No accounting for taste why we eat what we eat - De Robbio, Michael; Leunig, Sunny; McLean, Matthew; Nolan, Jane.; Video Education America ([Indianapolis, IN], Australia : VEA, 2011)
'The program investigates the factors that play significant roles in determining the foods we love and those we just can't stomach! With help from nutritionist Ros Ryan, and the experiences and opinions of everyday people from around the world, we reveal the physiological, psychological, social, and economic factors that affect our choice of foods.'--Container.
Voice over: Jane Nolan.
DVD format.
Keywords: Food preferences; Food habits; Taste